AIDS : abstracts of the psychological and behavioral literature, 1983-1989 - Jones, James M.; Kerby, Jody L.; Landry, Christine P. (Washington DC : American Psychological Association, 1989)
Fonds Suzan Daniel (FSD)
Engels
Monografie